Charakterystyka i zróżnicowanie funkcjonalne starorzeczy w dolinach dużych rzek nizinnych = The characteristics and functional diversity of oxbow lakes in large lowland river floodplains - Puchalski, Wojciech (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Oxbow lakes constitute an important element or the landscapc of lowland river floodplains. The structural characteristics and chosen aspects of biogeochemical functions are described for oxbow ecosystems in the lower Vistula floodplain, considering metabolic properties of bottom sediments and functions of aquatic vegetation. Typology of oxbow lakes, based mainly on their susceptibility to flood disturbances and on vegetation structure and diversity is proposed.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)